Negros, humanidade e religião em Brazil and the Brazilians – portrayed in historical and descriptive sketches / Negroes, humanity and religion in Brazil and the Brazilians – portrayed in historical and descriptive sketches - Oliveira, Débora Villela de (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
O artigo indica como na narrativa do livro Brazil and the Brazilians– portrayed in historical and descriptive sketches seus autores procuraram apresentar, nas imagens sobre os negros e escravos brasileiros, novas reflexões sobre o caráter do negro para leitores dos Estados Unidos da América, no pré-guerra civil norte-americana. Abstract This article indicates how, in the narrative of the book Brazil and the Brazilians – portrayed in historical and descriptive sketches, its authors intended to present, through images of Brazilian negro slaves, new thoughts about the negro character to the readers in the United States’ antebellum.